2018
DOI: 10.3390/jcs2040058
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Buckling Behaviour of Thin and Thick Variable-Stiffness Panels

Abstract: The possibility of designing composite panels with non-uniform stiffness properties offers a chance for achieving highly-efficient configurations. This is particularly true for buckling-prone structures, whose response can be shaped through a proper distribution of the membrane and bending stiffnesses. The thermal buckling behaviour of composite panels is among the aspects that could largely benefit from the adoption of a variable-stiffness design, but, in spite of that, it has rarely been addressed. The paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…From Table. 4, it is clear that the results of critical buckling temperature predicted by using the present Rayleigh-Ritz model are very close to those obtained by Vescovini and Dozio[48] and Zhao et al[54] and FE solutions for all the composite materials studied. The ability of the proposed Rayleigh-Ritz model to accurately predict the thermal buckling response of VAT composite plates is thus demonstrated.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…From Table. 4, it is clear that the results of critical buckling temperature predicted by using the present Rayleigh-Ritz model are very close to those obtained by Vescovini and Dozio[48] and Zhao et al[54] and FE solutions for all the composite materials studied. The ability of the proposed Rayleigh-Ritz model to accurately predict the thermal buckling response of VAT composite plates is thus demonstrated.…”
supporting
confidence: 88%
“…Recently, Haldar et al [47] extended the Rayleigh-Ritz minimization technique proposed by Dano and Hyer [22] to study thermally induced mul-tistable behavior of unsymmetric laminates with curvilinear fibre paths. Vescovini and Dozio [48] studied the thermal buckling of VAT composite plates in the framework of a variable-kinematics approach based on Carrera's Unified Formulation (CUF). In their work, closed-form solutions of prebuckling results are presented four different sets of inplane boundary constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages offered by VS laminates are well-known, and have been extensively studied with respect to their behavior in terms of mechanical buckling [1][2][3][4][5][6][7][8][9][10], thermal buckling [11][12][13], fundamental frequencies [14][15][16] and failure loads [5,17]. One side-effect of variable-stiffness configurations is the exponentially growing number of degrees of freedom, which requires special consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Potential gains offered by tow-steered panels are well-documented in the literature [1][2][3][4][5], and several studies clearly illustrated the possibility of improving buckling and postbuckling responses with respect to corresponding quasi-isotropic configurations. Recent works addressed also the effects of different kinematic theories when applied to the analysis of tow-steered panels [3,6,7]. In the past years, it was demonstrated that curvilinear stringers can be successfully used to further improve stiffness tailoring opportunities and, to a more general extent, the structural efficiency of stiffened panels.…”
Section: Introductionmentioning
confidence: 99%